Perbedaan Nilai Pasar Dan Kinerja Keuangan Perbankan Pada Saat Sebelum Dan Sesudah Covid 19 - Harsono Yoewono; Millenia Juliandari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze differences in market value and financial performance before and after covid 19, as well as their impact on stock returns. The research applies the associative method. the sample was determined using a saturated sampling method. research data uses secondary data in the form of financial reports. The data is presented in the form of financial reports and annual reports for banks that use basel III and IV between 2015 and 2022, sourced from the idx.co.id website. as independent variables, financial difficulties, credit risk, market risk, and capital adequacy ratio serve as proxies for financial performance. stock returns function as the dependent variable. multiple linear regression and paired sample t test were used to test the data. this research found that it was proven that there were differences in capital adequacy ratios and financial distress before and after covid 19, but the market performance of credit risk, market risk and stock returns was proven to be no different before and after covid 19. the research results also found: (1) the capital adequacy ratio has an impact on stock returns; (2) credit risk has no impact on stock returns; (3) market risk has an impact on stock returns; and (4) financial distress indicators have an impact on stock returns at banks included in book 3 banks and book 4 banks that implement basel in indonesia. Keywords: Capital Adequacy Ratio, Credit Risk, Market Risk, Financial Distress, Stock Returns, Basel Jel Classification: G21